Reliability in Scientific Research : Improving the Dependability of Measurements, Calculations, Equipment, and Software - Walker, I. R. (Cambridge : Cambridge University Press, 2011)
Covering many techniques widely used in research, this book will help researchers in the physical sciences and engineering solve troublesome - and potentially very time consuming - problems in their work. The book deals with technical difficulties that often arise unexpectedly during the use of various common experimental methods, as well as with human error. It provides preventive measures and solutions for such problems, thereby saving valuable time for researchers. Some of the topics covered are: sudden leaks in vacuum systems, electromagnetic interference in electronic instruments, vibrations in sensitive equipment, and bugs in computer software. The book also discusses mistakes in mathematical calculations, and pitfalls in designing and carrying out experiments. Each chapter contains a summary of its key points, to give a quick overview of important potential problems and their solutions in a given area.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Statistics